Comments on "Structure origin of a transition of classic-to-avalanche nucleation in Zr-Cu-Al bulk metallic glasses". (1st April 2019) - Altounian, Z.; Strom-Olsen, J.O.; Ryan, D.H.
Abstract: In a recent paper, Lan et al. (Acta Materialia 149 (2018) 108) claim to have observed avalanche-type nucleation during the crystallization of Zr-Cu-Al bulk glasses. They based their claims on their interpretation of differential scanning calorimetry, X-ray and neutron diffractometry and transition electron microscopy data. This particular type of crystallization kinetics has been observed before in many other studies on the crystallization of a wide range of metallic glasses but which, for unknown reasons, have not been cited by Lan et al. These earlier studies showed that the anomalous crystallization kinetics were actually due to the nucleation and rapid growth of a crystalline phase around quenched-in nuclei associated with the presence of oxygen and other impurities. In this comment, we intend to clarify the discrepancies reported by these different studies.